1976
DOI: 10.1007/bf00149859
|View full text |Cite
|
Sign up to set email alerts
|

Coronal holes as sources of solar wind

Abstract: We investigate the association of high-speed solar wind with coronal holes during the Skylab mission by: (1) direct comparison of solar wind and coronal X-ray data; (2) comparison of nearequatorial coronal hole area with maximum solar wind velocity in the associated streams; and (3) examination of the correlation between solar and interplanetary magnetic polarities. We find that all large near-equatorial coronal holes seen during the Skylab period were associated with high-velocity solar wind streams observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
215
1
4

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(234 citation statements)
references
References 15 publications
14
215
1
4
Order By: Relevance
“…It was discovered during the 1970s from Skylab data that high-speed solar wind streams originate from large coronal holes (Krieger et al, 1973;Nolte et al, 1976;Zirker, 1977). Wang and Sheeley Jr (1990) investigated the empirical relationship between solar wind speed patterns and the magnetic field structure at the solar wind source location.…”
Section: Relationship Between Coronal Hole Structure and Solar Wind Smentioning
confidence: 99%
See 1 more Smart Citation
“…It was discovered during the 1970s from Skylab data that high-speed solar wind streams originate from large coronal holes (Krieger et al, 1973;Nolte et al, 1976;Zirker, 1977). Wang and Sheeley Jr (1990) investigated the empirical relationship between solar wind speed patterns and the magnetic field structure at the solar wind source location.…”
Section: Relationship Between Coronal Hole Structure and Solar Wind Smentioning
confidence: 99%
“…Crucially, a strong correlation was found between the average unsigned photospheric field strength in open-field regions and the solar wind speed at 1 AU. Nolte et al (1976) had demonstrated that the areas of large equatorial coronal holes are correlated with the maximum speeds of the associated solar wind streams, a pattern that Levine et al (1977) interpreted in terms of expanding flux tubes: high-speed winds originate from the centers of large holes because flux tube expansion is minimal there. This suggested that the solar wind flow could be treated in a manner similar to de Laval nozzle theory, in which con- Blue and yellow shading denote positive and negative polarities, respectively.…”
Section: Relationship Between Coronal Hole Structure and Solar Wind Smentioning
confidence: 99%
“…Because of the strong association between coronal holes and high-speed solar wind streams which has been known since the 1970s (see, e.g., Krieger, Timothy, and Roelof, 1973;Neupert and Pizzo, 1974;Nolte et al, 1976;Zirker, 1977), and because of the detection of blue shift within coronal holes in coronal and transition region lines indicating outflow (see, e.g., Hassler et al, 1999;Peter and Judge, 1999;Xia, Marsch, and Curdt, 2003;Aiouaz, Peter, and Lamaire, 2005) coronal holes are usually identified as the sources of the fast wind from where the wind flows out in the corona and is accelerated in expanding magnetic funnels (Tu et al, 2005). However, in coronal models, the term coronal holes is often used to more generally indicate the foot-points of the magnetic field lines "open" to the heliosphere.…”
Section: Coronal Holesmentioning
confidence: 99%
“…HSSs originate from coronal holes (CHs) on the Sun (Krieger, Timothy, and Roelof, 1973). Since the 1970s, CHs are known for being long-lived and rigidly rotating phenomena in the solar corona (Krieger, Timothy, and Roelof, 1973;Neupert and Pizzo, 1974;Nolte et al, 1976), magnetically "open" to interplanetary space, allowing the solar wind particles to escape from the Sun (Tsurutani et al, 1995;Gosling and Pizzo, 1999;Cranmer, 2009). The plasma temperature and density in CHs is low compared to their surroundings, and thus they appear as dark areas in the corona (Munro and Withbroe, 1972;Cranmer, 2009).…”
Section: Introductionmentioning
confidence: 99%